Pengaruh Content Marketing, Brand Image dan Electronic Word of Mouth pada Purchase Intention Produk Hand Body Scarlett - Dzin Nada Arzaqiyah; Wenti Krisnawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the influence of content marketing, brand image, and electronic word of mouth (EWOM) on consumer purchase intention for Scarlett hand body products in Gresik. The research adopts a quantitative approach using surveys with 200 respondents selected through purposive sampling. Data were analyzed using multiple linear regression methods. The findings reveal that all three independent variables significantly influence consumer purchase intention. The study concludes with recommendations for Scarlett to enhance its social media-based marketing strategies and strengthen brand image through creative content.